Records of the crowned eagle (Urubitinga coronata) in Moxos plains of Bolivia and observations about breeding behavior - Berkunsky, Igor (2012)
The Crowned Eagle (Urubitinga coronata, Accipitridae) is a globally endangered raptor, endemic to central and southern South America. Little is known about this species in Bolivia and no nesting or prey data have been reported for the country until now. Between 2007 and 2011, we detected Crowned Eagles in four different locations in Moxos Savannahs of Beni Department, Bolivia. We observed an active nest of Crowned Eagle on 23 November 2007. The nest contained a nestling and it was placed on a living tree approximately 13 m in height and approximately 8 m above the ground. This nest was empty during September and October 2008, but contained another nestling on 15 November 2009. These represent the first breeding records for the Crowned Eagle in Bolivia. Prey remains at the nest observed included two nine-banded armadillos (Dasypus novemcinctus) and two six-banded armadillos (Euphractus sexcinctus). The minimum number of individual Crowned Eagles in the surveyed area was seven. Our observations of family groups, juveniles and two nestlings confirm the breeding of Crowned Eagles in the Moxos plains. Ectoparasites and uncontrolled burns may threaten the northwestern Bolivian population of the endangered Crowned Eagle.